ADOPTION OF DIGITAL MARKETING IN BUSINESS DEVELOPMENT EFFORTS : IMPACT AND CHALLENGES FOR MICRO, SMALL AND MEDIUM ENTERPRISES - Muh. Husriadi; La Ode Abdul Musawir, La Ode Ahmad Darwin, Kasman Muslimin (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
Given the challenges of increasingly competitive markets, the use of digital marketing is becoming increasingly important for micro, small and medium enterprises (MSMEs). This research aims to determine the role of digital marketing in the development of MSMEs in Wua-wua and Kambu Districts, Kendari City. Using a qualitative approach, data was collected through in-depth interviews with MSME owners who actively utilize digital marketing. Findings show that the implementation of digital marketing has increased online sales, expanded market reach and increased brand awareness. The biggest challenges in implementing digital marketing include limited budget, lack of knowledge, and limited resources. The findings conclude that to strengthen the digital capabilities of MSMEs and ensure their sustainability in an increasingly digital market, the government needs to require further support from the government and related organizations.